2021
DOI: 10.3389/fimmu.2021.688659
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Mast Cells in Response to Fungal Infection

Abstract: Mast cells (MCs) have been considered as the core effector cells of allergic diseases. However, there are evidence suggesting that MCs are involved in the mechanisms of fungal infection. MCs are mostly located in the border between host and environment and thus may have easy contact with the external environmental pathogens. These cells express receptors which can recognize pathogen-associated molecular patterns such as Toll-like receptors (TLR2/4) and C-type Lectins receptors (Dectin-1/2). Currently, more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Innate activation through Dectin-1/CARD9 facilitating IL-1β, IL-6, and IL-23 secretion by dendritic cells is critical for disseminating adaptive antifungal Th17-cell responses [31]. A deficiency of Dectin-1 increases the risk of infectious diseases and thus reflects its pivotal role in immune defense [154].…”
Section: Established Immune Mechanisms In Candida Associated Co-morbi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Innate activation through Dectin-1/CARD9 facilitating IL-1β, IL-6, and IL-23 secretion by dendritic cells is critical for disseminating adaptive antifungal Th17-cell responses [31]. A deficiency of Dectin-1 increases the risk of infectious diseases and thus reflects its pivotal role in immune defense [154].…”
Section: Established Immune Mechanisms In Candida Associated Co-morbi...mentioning
confidence: 99%
“…These events induce the assembly of a scaffold comprising of caspase-recruitment domain 9 (CARD9), adaptor-protein B-cell lymophoma-10 (Bcl-10) and mucosa-associated lymphoid-tissue-lymphoma-translocation protein 1 (MALT1) [27][28][29]. The assembly and activation of the CARD9/Bcl-10/MALT1 complex activates the canonical NF-κB pathway leading to the release of various proinflammatory cytokines and reactive oxygen species (ROS) production, thereby triggering phagocytosis (Figure 1) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…gastrointestinal tract), are the first defense cells to interact with allergens, invading pathogens and other dangerous antigens. 12 , 13 Substantial evidence showed that MCs played a crucial role in fibrotic diseases. 14 However, their explicit effects on CD fibrosis remain unknown.…”
Section: Search Strategymentioning
confidence: 99%
“…Among PRRs expressed on MCs, there are also molecules from the CLR group or some TLRs, which may sense different fungal components (Figure 2) [30]. However, little information exists concerning MC involvement in antifungal host defense, and the function of MCs in fungal infections is not precisely defined [31,32].…”
Section: How Do Mcs Contribute To the Host Defense?mentioning
confidence: 99%